Construction Design Consultant Selection Using The Analytic Network Process Method - Kusuma Ariftama; Athor Subroto (UNIVED Press, 2024)
This research aims to analyze what criteria and subcriteria are important to use in assessing prospective Construction Design Consultant in the procurement process using the ANP method. This research departs from the problem that the Toll Road Planning Division, which is responsible for technical and financial planning for the Trans Sumatra Toll Road project, is not spared from vendor performance problems, where in recent years several Construction Design Consultant have not managed to complete their work with the right quality and time. The results showed that the priority criteria for selecting the best construction design consultant are Quality of Service (23.31%), Relationship with Job Owner (22.36%), Company Certification (20.87%), Quality of Personnel (20.55%), and Company Reputation (12.91%). The subcriteria that has the highest weight is the Personality of personnel (14.90%) and the lowest is the Availability of software (0.75%). The sensitivity analysis of alternative priority weights shows that there is no change in the priority order of alternatives if the subcriteria weights are changed by amounts ranging from -50% to +40%.